2008
DOI: 10.1002/jmv.21389
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tick‐borne encephalitis virus in Ixodes Ricinus from a novel endemic area of North Eastern Italy

Abstract: In Alpine area of extreme North Eastern Italy the first autochthonous case of TBE was reported in 1998 and was followed by 45 cases during the period 2001-2007, thus defining this area as definitely endemic. An ecological survey evaluated the tick density and the Tick-borne encephalitis virus (TBEV) infection prevalence in tick collected in selected sites. In addition, TBE strains were characterized by sequencing and phylogenetic analysis. Overall, 2,361 ticks (2,198 nymphs and 163 adults) of the Ixodes ricinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
5
12
1
Order By: Relevance
“…The Bayesian phylogenetic analyses provide results that are consistent with those of previous studies, indicating that the new Italian TBEV sequences generated here belong to the European TBEV subtype (Hudson et al, 2001;D'Agaro et al, 2009). Interestingly, we found a substantial amount of genetic divergence between these Italian TBEV sequences, despite both the relatively short E gene sequence fragments analysed and the restricted geographical range (Trento province only).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The Bayesian phylogenetic analyses provide results that are consistent with those of previous studies, indicating that the new Italian TBEV sequences generated here belong to the European TBEV subtype (Hudson et al, 2001;D'Agaro et al, 2009). Interestingly, we found a substantial amount of genetic divergence between these Italian TBEV sequences, despite both the relatively short E gene sequence fragments analysed and the restricted geographical range (Trento province only).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the incidence of TBE in these regions has increased from 0.06 to 0.88 cases per 100 000 inhabitants in the same time frame (Rizzoli et al, 2009). Importantly, TBEV has been isolated and identified in most of the regions where human cases have been reported (Hudson et al, 2001;Beltrame et al, 2006;Cruciatti et al, 2006;Floris et al, 2006;D'Agaro et al, 2009). However, previous studies undertaken primarily in the Veneto and Trentino regions have shown a lower prevalence of TBEV in Italian tick populations compared with other European sites where TBEV is endemic (Hudson et al, 2001), whilst phylogenetic analyses indicate that only strains of the European subtype very similar to the Austrian Neudoerfl strain have been found in Italian TBEV populations (Hudson et al, 2001;Floris et al, 2006;D'Agaro et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study was carried out in a mountain area of northeastern Italy, where both Lyme borreliosis and TBE are endemic (D'Agaro et al, 2009;Nazzi et al, 2010). Climate is cool temperate, with annual precipitations around 2800 mm per year and an average annual mean temperature around 11 • C. Vast mixed woodlands cover most of the area and some open meadows are located around villages.…”
Section: Study Areamentioning
confidence: 99%
“…"Annales ofAgricultural and Environmental Medicine 16,[211][212][213][214][215][216][217] 110 "Bitam I, Parola P,Matsumoto K, Rolain J M, Baziz B, Boubidi S C, Harrat Z, Belkaid M and Raoult D, 2006. " Occurrence of Borrelia burgdorferi sensulato in Ixodes ricinus and Dermacentor reticulatus ticks collected from roe deer and deer shot in the south-east of Poland.…”
mentioning
confidence: 99%